Fuzzy multi-objective mathematical programming on reliability optimization model - Mahapatra, G.S.; Roy, T.K. (Applied mathematics and computation, 2006)
This paper considers multi-objective reliability optimization problem for system reliability where reliability enhancement is involved with several mutually conflicting objectives. It is conflicting to reduce the cost of the system and improve the reliability of the same system simultaneously. A new fuzzy multi-objective optimization method is introduced and it is used for the optimization decision making of the series and complex system reliability with two objectives. In general, cost of the components of the system’s objective goals has not been stated clearly. This imprecise reliability optimization model is solved through the fuzzy multi-objective optimization method. Examples are shown to illustrate the method.